MANAJEMEN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Sugeng Utomo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2011)
Abstract: The purpose of this descriptive quantitative research was to test elementary school teachers competency in teaching social studies education, i.e. planning, implementing, and interpersonal relation. Locations of the research were SD Negeri Bareng I and II Malang City. Subjects of the research were four elementary schools social studies education teachers, two principals, and forty students. The data were collected by participant observation, in depth interview, documents study, audio recording, and photo. The results of the research were (1) competency in planning of teaching was in the middle grade (2) competency in implementing of teaching was in the middle grade (3) competency in interpersonal relation generally was good (4) factors influenced competency of teaching social studies education were teachers’ professionalism skills and creativity.Abstrak: Penelitian deskriptif-kualitatif ini bertujuan untuk menguji kemampuan guru SD dalam pembelajaran IPS, meliputi perencanaan, pelaksanaan, dan hubungan antarpribadi. Lokasi di SD Negeri Bareng I dan II Kota Malang. Subyek penelitian diambil empat guru IPS kelas 4 dan 5, dua kepala sekolah, dan 40 siswa di sekolah tersebut. Teknik pengumpulan data dilakukan dengan observasi partisipan, wawancara mendalam, studi dokumen, perekaman dengan tape recorder, dan fotografi. Hasil penelitian menunjukkan (1) kemampuan merancang pembelajaran rata-rata cukup; (2) kemampuan melaksanakan pembelajaran cukup, (3) kemampuan hubungan antarpribadi umumnya baik, dan (4) faktor faktor yang mempengaruhi kemampuan pembelajaran IPS adalah kemampuan profesionalisme dan kreativitas guru.